pawsusana
pawsusana
10-05-2017
Mathematics
contestada
Elimination
y= -x-1
y= -5x-17
Respuesta :
mreijepatmat
mreijepatmat
15-05-2017
y= -x-1
y= -5x-17 Multiply the 1st equation by (-1) & then add up the result to the 2nd one:
-y = -1(-x) -1(-1)
y = -5x-17
-----------------
0y = -4x-16 ===> x=-4 & y=3
Answer Link
VER TODAS LAS RESPUESTAS ( 87+ )
Otras preguntas
13. Describe how you could make a sound wave have a higher VOLUME. Describe how you could make a sound wave have a higher PITCH
About how many plant cells are there in A Leaf
If the pattern continues how many cups of milk does George need to make 6 batches of muffins
A map suggests that Atlanta is d1 = 729 mi in a direction of θ1 = 5.11° north of east from Dallas. The same map shows that Chicago is d2 = 562 miles in a direct
How could you increase the sliding friction between the sled and track? How could you decrease it?
Help With This Jawn Please
A full endorsement on a check A.is the same as a blank endorsement B.can be endorsed only by the person or company names in the original endorsement C. Is the
True or false??? The constitution prohibits the president from giving information or making recommendations to Congress Help pleasee
According to john locke what is the purpose of government
which is a good source for calcium? A)berries B)legumes C)root vegetables D)whole wheat